Comprehensive emergency management of obstetric and newborn care program implementation at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2021: an evaluation study - Melak Jejaw; Ayal Debie; Lake Yazachew; Getachew Teshale (BMC, 2023)
Abstract Background Maternal healthcare service is the care given for the woman during her gestation, delivery and postpartum period. The Maternal Mortality Ratio (MMR) was remains high and a public health problem in Ethiopia. Sub-Saharan African (SSA) countries account two-thirds of the global total maternal deaths. To curb such high burden related with child births, comprehensive emergency obstetric care is designed as one of the strategies for maternal healthcare services. However, its implementation status was not well investigated. This study aims to evaluate the implementation of comprehensive emergency obstetric and new born care program in terms of Availability, compliance and acceptability dimensions at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Methods A single case study design was employed from 01 to 30 April 2021. A total of 265 mothers who gave birth at University of Gondar Comprehensive Specialized Hospital (UoGCSH) during the data collection period for acceptability, 13 key informant interviews (KIIs), 49 non-participatory observations (25 observations during C/S performance and 24 assisted spontaneous vaginal deliver) and 320 retrospective document review were conducted. Availability, compliance and acceptability dimensions were evaluated using 32 indicators. Binary logistic regression model was fitted to identify factors associated with acceptability of the services. Adjusted Odds Ratio (AOR) with 95% confidence interval (CI) and p-value < 0.05 were also used to identify associated variables with acceptability. The qualitative data were recorded using tape recorder, transcribed in Amharic and translated to English language. Thematic analysis was done to supplement the quantitative findings. Results The overall implementation of comprehensive emergency obstetric and newborn care (CEmONC) was 81.6%. Moreover, acceptability, availability and care provider's compliance with the guideline accounted 81, 88.9 and 74.8%, respectively. There were stocked-out of some essential drugs, such as methyldopa, nifidipine, gentamycin and vitamin K injection. CEmONC training gaps, inadequate number of autoclaves, shortage of water supply and long-distance delivery ward to laboratory unit were also the barriers for the CEmONC service. Short waiting time of clients (AOR = 2.40; 95%CI: 1.16, 4.90) and maternal educational level (AOR = 5.50, 95%CI: 1.95, 15.60) were positively associated with acceptability of CEmONC services. Conclusion The implementation status of CEmONC program was good as per our judgment parameter. Compliance of healthcare providers with the guideline was fair and needed improvement. Essential emergency drugs, equipment and supplies were stocked-out. The University of Gondar Comprehensive Specialized Hospital was therefore had better to give great emphasis to expand maternity rooms/ units. The hospital had better to avail the resources and provide continuous capacity building for healthcare providers to enhance the program implementation.